THE INFLUENCE OF TEACHING METHOD, EMOTIONAL INTELLIGENCE AND ADVERSITY INTELLIGENCE OF STUDENTS LEARNING OUTCOME VIDEOGRAPHY - Supriyadi Supriyadi; Suyono Suyono; Nurjannah Nurjannah (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2017)
This research used experimental method. The sampling technique used cluster random sampling. The sample of this research is 120 students that distinguished on students who have high emotional intelligence and climber type adversity intelligence, high emotional intelligence and quitter type adversity intelligence, low emotional intelligence and have climber adversity type and low emotional intelligence and have quitter type adversity intelligence. The result of try out the instrument show that the reliability of research instrument are follows: the instrument of learning result of videography of 0.918, the instrument of emotional intelligence dimension I of 0.879, dimension II of 0.805. 1 dimensional instrument of 0.850, II of 0.350, III of 0.742 and IV of 0.717. Analysis of the data used two lane ANAVA 2X2X2. The results of this research are as follows: (1) The learning approach influences the learning outcomes of videography. (2) Emotional intelligence affects the learning outcomes of videography. (3) Adversity intelligence affects the learning outcomes of videography. (4) There is an interaction effect between learning approach and emotional intelligence on learning result of videography. (5) There is interaction influence of learning approach and adversity intelligence to learning result of videography. (6) There is no influence of emotional intelligence interaction and adversity intelligence on learning result of videography. (7) There is an interaction effect of learning approach, emotional intelligence, and adversity intelligence to learning result of videography. Keywords: Emotional Intelligence, Adversity Intelligence, Videography